Coronary stent deployment in situs inversus. Issue 5 (1st November 2001) - Robinson, N; Golledge, P; Timmis, A
Abstract : Situs inversus with dextrocardia occurs in approximately one in 10 000 patients. Successful stent deployment for the treatment of unstable angina and situs inversus is presented. Three technical challenges associated with the procedure are highlighted. Firstly, the successful choice of diagnostic and interventional catheters is based on an understanding of the orientation of the aortic arch. With a right sided aorta Judkins catheters should be successful. Secondly, image reversal is not necessarily required for image interpretation. Thirdly, successful coronary engagement with catheters requires rotation in a direction opposite to that normally used.